An electrochemical quartz crystal microbalance study of the electrochemistry of 4,4'-bipyridyl at silver electrodes. - Pisharodi, Devi. (University of Ottawa (Canada), 1995)
This thesis describes the application of the Electrochemical Quartz Crystal Microbalance (EQCM) technique to the study of the electrochemistry of 4,4$\sp\prime$bipyridyl at silver electrodes. The Ag-Bpy system was originally studied because Bpy was found to act as a promoter for the redox protein cytochrome c when adsorbed at silver electrodes. The system is also reported to display many phenomena (such as complex and film formation) that should be observable with the EQCM. Chapter 3 describes a study of the oxidation of Ag in the presence of 4,4$\sp\prime\rm bipyridyl$ where the Ag$\sp+$ and bipyridyl form a complex. The observed mass changes are found to result from the superposition of a mass loss due to the release of Ag$\sp+$ into solution and a mass gain from complex precipitation. When higher concentrations of Bpy (2mM) are used, complex formation is the dominant process that contributes to the mass change and so a simple mass increase is seen until the potential is extended further positive such that the surface concentration of bipyridyl is depleted significantly. Electrode corrosion then becomes the principal process causing the observed mass change to be a net decrease. In Chapter 4, the reduction of 4,4$\sp\prime$bipyridyl was studied at electrodeposited Ag electrodes in 0.1M Na$\sb2$SO$\sb4.$ Thus in contrast to the oxidation experiments where silver is the redox active species, it is the bipyridyl that is the redox active species in the reduction experiments. At high negative potentials a film of reduced Bpy develops on the electrode surface and its growth, development and removal can be observed and controlled by monitoring the mass responses. Both systems studied provide an illustration of the extra insight into surface processes at electrodes that the EQCM method provides, relative to cyclic voltammetry alone. (Abstract shortened by UMI.)
Keywords: Chemistry, Physical.